2007
DOI: 10.1007/s00109-007-0242-x
|View full text |Cite
|
Sign up to set email alerts
|

VMAT2 gene expression and function as it applies to imaging β-cell mass

Abstract: Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. The two main forms of the disease are distinguished by different pathogenesis, natural histories, and population distributions and indicated as either type 1 (T1DM) or type 2 diabetes mellitus (T2DM). It is well established that T1DM is an autoimmune disease whereby beta-cells of pancreatic islets are destroyed leading to loss of endogenous insulin production. Albeit less dramatic, beta-cell mass (BCM) also drops in T2DM. Therefore, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 125 publications
0
41
0
Order By: Relevance
“…Ideally, two basic criteria should be met for adequate beta cell imaging [6]: (1) beta cells should retain the tracer 100-to 1,000-fold more than the exocrine cells; and (2) agents that label beta cell surface proteins should do this at high enough concentrations to overcome imaging signals arising from unbound tracer retained in the extracellular and vascular spaces, and from tracer bound to the other tissues surrounding the pancreas. Agents being tested currently for BCM imaging include glibenclamide [6], glucagon-like peptide 1 receptor [7,8], sulfonylurea receptor [6], vesicular monoamine transporter 2 (VMAT2) [9][10][11][12][13] and gangliosides [14]. Unfortunately, the uptake/binding of these agents to beta cells, compared with exocrine pancreas and non-beta cells, is insufficient to allow reliable imaging of the BCM [6,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, two basic criteria should be met for adequate beta cell imaging [6]: (1) beta cells should retain the tracer 100-to 1,000-fold more than the exocrine cells; and (2) agents that label beta cell surface proteins should do this at high enough concentrations to overcome imaging signals arising from unbound tracer retained in the extracellular and vascular spaces, and from tracer bound to the other tissues surrounding the pancreas. Agents being tested currently for BCM imaging include glibenclamide [6], glucagon-like peptide 1 receptor [7,8], sulfonylurea receptor [6], vesicular monoamine transporter 2 (VMAT2) [9][10][11][12][13] and gangliosides [14]. Unfortunately, the uptake/binding of these agents to beta cells, compared with exocrine pancreas and non-beta cells, is insufficient to allow reliable imaging of the BCM [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the uptake/binding of these agents to beta cells, compared with exocrine pancreas and non-beta cells, is insufficient to allow reliable imaging of the BCM [6,15]. For instance, the most promising beta cell marker, VMAT2, is produced in beta cells and monoaminergic neurons [10] but recent studies indicate that VMAT2 is also present in other islet cells besides beta cells [13]. Promising preliminary data were obtained with 11 C-labelled dihydrotetrabenazine (the PET ligand binding specifically to VMAT2) in streptozotocin (STZ)-induced diabetic Lewis rats [11] and in the BB-DP rat [12], but the data obtained in baboons [15] and in patients with longstanding type 1 diabetes [16] are not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previously developed β-cell-specific imaging agents have included labeled glucose analogs (or other small molecules) (1,2), antibodies (3), sulfonylureas (2,4), and vesicular monoamine transporter receptor agonists (5,6). In addition, a variety of transgenic strategies have been applied to mouse models (7,8).…”
mentioning
confidence: 99%
“…44,45 to produce a significant amount of insulin. 49 The Diabetes control and complications trial (DCCT) found that 20 % of patients studied, who were within five years of diagnosis, had remaining endogenous insulin production as measured by C-peptide levels; 50 within the first five years after diagnosis, immunologic intervention can potentially save β-cell function and reduce reliance on insulin administration.…”
Section: Pancreatic Pathologymentioning
confidence: 99%